Single Molecule Microscopy Is Useful Technique For DNA Hairpin FRET Systems. - Mohammed, Asma Hadi (Al-Nahrain Journal of Science, 2018)
Nanometre sized semiconductor quantum dots as fluorescent materials are now becoming as ubiquitous as the organic dyes that preceded them. By virtue of their tuneable optical properties, narrow emission profiles and photostability, QDs have proved themselves as resilient and multifarious in both their applications and their underlying photophysics compared to their organic dye counterparts. Single Molecule Microscopy techniques (SM) are especially relevant to macromolecular biochemistry as chemical processes occurring within large molecules that are often too complicated to study in the ensemble. Using both total internal reflection (TIR) and Confocal Microscopy (CM) and both image processing and photon counting to achieve understanding of the binding kinetics and dynamic properties exhibited by the molecule via FRET studies. Several versions of the system have been examined to optimize the FRET pairing of donor/acceptor tags, achieve quantitative and ratiometric bioconjugation to nanocrystals and perfect techniques of microscopy and image processing.